A potential gas sensor device based on Pd/RGO/TiO2 nanotube ternary hybrid junction. (November 2017) - Ghosal, S.; Bhattacharyya, P.
Abstract: In the present work, fabrication, characterizations and gas sensing performance of a novel ternary hybrid junction device consisting of Pd nanoparticles, Reduced Graphene Oxide (RGO) and TiO2 nanotubes (NTs) is reported. Electrochemically derived TiO2 nanotubes were covered partially by RGO matrix in the form of distributed islands, on top of which Pd nanoparticles were dispersed uniformly. After detailed structural and morphological characterizations, gas sensing potentiality of the developed ternary hybrid device was tested for detection of methanol vapor and the sensing performance was compared with that of the RGO-TiO2 binary structure to ensure the improvement caused by incorporation of the ternary element (Pd). Underlying mechanistic framework for gas sensing, by such ternary junction, was explained with the help of corresponding energy band diagram. Graphical abstract: Highlights: Pd/RGO/TiO2 nanotube ternary hybrid device was fabricated. The sensor was tested (27–100 °C) for the detection of methanol (10–700 ppm). Response magnitude of ~ 96.3% was obtained at 50 °C with response/recovery of 11 s/15 s, respectively. Band diagram of Pd/RGO/TiO2 junction was developed to describe the gas sensing mechanism.